Direito à prisão no Brasil contemporâneo: limites e possibilidades da remição penal - Amaral, Bruno Falci (2024)
Prison life is the concrete expression of how societies have created/create mechanisms that allow theoretical and practical responses to the objective/subjective conditions in which the incarcerated person finds himself in a given historical period. This study/research, delimited in time and space from 2016 to 2023, in Brazil, addresses the programs implemented in the Brazilian prison system related to education and work as mechanisms for reducing sentences through remission, as provided for in the Penal Enforcement Law. The chosen object of this study are the programs implemented in the Brazilian prison system related to education and work, understood as mechanisms for reducing sentences through remission. To this end, the general objective is, therefore, to apprehend, understand and analyze the programs for remission of sentences through education and work, embodied in the Penal Enforcement Law, from the perspective of the implementation of fundamental constitutional rights. Based on the context surrounding the object and objective of the study/research, the research problem is to what extent programs related to education and work as means of reducing sentences, fulfill through statistical research, in addition to the reduction itself, the purpose of creating a process of resocialization in the subject deprived of liberty in this factual context. The study/research was developed based on the theoretical-practical framework and current legislation pertinent to the topic. Thus, the research approach was exploratory in nature based on bibliographic sources and documentary research. As a response to the research problem, it is clear that education and work programs fulfill, solely, the role of reducing the time of deprivation of liberty. After following this path, it was found that the Brazilian prison system guarantees, albeit in a limited way, the remission of sentences through education and work, even though such programs are devoid of the biases of emancipation and social reintegration.